Protection of intellectual property in Hungarian jurisprudence of the 19th century - Nótári, Tamás (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
Given the peculiarities of historical development, modern codification efforts evolved with a delay in the Age of Reforms in the eighteen-thirties; with respect to copyright the Bills related to Bertalan Szemere are worth mentioning. After suppression of the War of Independence (1849) and the Compromise (1867), basically Austrian laws were applied. The history of Hungarian copyright law is characterised both by successful and unsuccessful attempts at codification, although aborted bills failed due to changes in historical circumstances rather than the standard of proposals. The Bill submitted by Bertalan Szemere to the National Assembly in 1844 was not enacted for lack of royal sanctioning. Following the age of imperial patents and decrees, after the Compromise (1867) the Society of Hungarian Writers and Artists put forth—again an unsuccessful—motion for regulation; however, the Commercial Code, Act XXXVII of 1875 devoted a separate chapter to regulation of publishing transactions. The first Hungarian copyright law, Act XVI of 1884, was made following László Arany’s initiative, upon István Apáthy’s motion. The Act implemented modern codification adjusted to bourgeois conditions, setting out from theoretical bases of intellectual property not superseded ever since. In this paper first, we will the suggestions of Ferenc Toldy on protection of intellectual property, then we will examine the early stages of statutory protection of author’s works in Hungary, and finally, we will analyse the discuss Bertalan Szemere’s role in regulation of copyright and his 1844 Copyright Bill
Keywords: Bertalan Szemere; Ferenc Toldy; Hungarian law of copyright; intellectual property